Ownership Structure and Firm Performance with Moderating Role of Financing Decisions: Evidence from Listed Companies in Sri Lanka - Balagobei, S.; Subramaniam, V.A.; Saseela, B. (Uva Wellassa University, 2024)
The aim of this study is to examine the impact of ownership structure on the firm performance of listed companies in Sri Lanka. This investigation also intends to examine the moderating effect of financing decisions on the relationship between the ownership structure and the firm performance. This study was confined to listed companies using a sample of 100 companies in Sri Lanka with 900 firm-year observations from 2013 to 2021. Quantitative method and deductive approach were employed. Data were collected from the audited annual financial statements of the listed firms in CSE. The statistical techniques of Pearson’s correlation and panel data regression were used to analyze the association between the ownership structure and the firm performance. The findings of this study reveal that managerial ownership has a positive impact on the firm performance in terms of return on assets. Furthermore, financing decisions have a direct negative impact on return on assets and it moderates the nexus between institutional ownership and return on assets. When the firm’s debt level decreases, the effect of institutional ownership on return on assets will be more favourable to the listed companies. Similarly, financing decisions moderate the nexus between managerial ownership and return on assets. The coefficient of interaction affirms a negative and statistically significant effect of the interaction between financing decisions and managerial ownership. Moreover, it is found that financing decisions moderates negatively the nexus between foreign ownership and Tobin’s Q. The study recommends that the companies can use the less level of debt because it decreases the performance of companies in Sri Lanka. They should rely more on their internal source of finance. Furthermore, it is suggested that the listed firms may focus on prudent debt management and engage carefully in evaluating and controlling their debt levels to avoid adverse effects on performance. The firms can issue the shares to managers as it helps to reduce the agency cost and increase the firm performance. This study has broad and comprehensive practical implications which are beneficial for policymakers.
Keywords: Firm performance; Foreign ownership; Institutional ownership; Managerial ownership; Ownership concentration